A sub-word-parallel Galois field multiply-accumulate unit for digital signal processors - Roy, S. (2005 IEEE International Symposium on Circuits and Systems (ISCAS), 2005)
This paper presents a versatile Galois field multiply-accumulate (MAC) unit, which is used as a compute block in a digital signal processor (DSP). The MAC unit can be used to perform error detection through parallel computation of cyclic redundancy checks (CRC). We propose a Galois field MAC based algorithm to perform parallel computation of m-bit CRC using i bits of the message at a time, where i /spl les/ m. Handling less than m bits in parallel enables a trade-off by significantly reducing the hardware area and delay of the compute block. The MAC can also be used to perform error correction employing Reed Solomon codes. It uses a sub-word-parallel architecture to optimise the performance of the proposed CRC algorithm and Reed Solomon encoding/decoding. Thus it enables programmable solution to a large variety of applications employing error control coding techniques in the communications and consumer electronics field.